2004
DOI: 10.2131/jts.29.137
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Experimental Iodine Allergy: 2. Iodinated Protein Antigens and Their Generation From Inorganic and Organic Iodine-Containing Chemicals

Abstract: -We hypothesize that iodine allergy is an immune response to iodinated autologous proteins generated in vivo from iodine-containing organic and inorganic chemicals. In this report, effects of protein iodination on elicitogenic activity in guinea pig iodine allergy model and iodinated protein antigen generation in vitro from iodine-containing chemicals were investigated.Active cutaneous anaphylaxis (ACA) and delayed-type hypersensitivity (DTH) tests were performed in guinea pigs immunized with iodine. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Dermatologic side effects reported are acneiform eruption, iodermas (erythematous, vesicular, bullous, urticarial, nodular or vegetating lesions on the face, shoul-der, and extremities) (14), and worsening of dermatitis herpetiforme (15). Rare side effects are periarteritis nodosa, pustular psoriasis (16), and granulomatous vasculitis (17); their pathophysiology is unclear (18,19). In particular, the mechanism of the reaction observed in our case is unknown, and it is possible that the acute mucositis may be the result of a direct reaction to the high dose of iodine rather than to hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatologic side effects reported are acneiform eruption, iodermas (erythematous, vesicular, bullous, urticarial, nodular or vegetating lesions on the face, shoul-der, and extremities) (14), and worsening of dermatitis herpetiforme (15). Rare side effects are periarteritis nodosa, pustular psoriasis (16), and granulomatous vasculitis (17); their pathophysiology is unclear (18,19). In particular, the mechanism of the reaction observed in our case is unknown, and it is possible that the acute mucositis may be the result of a direct reaction to the high dose of iodine rather than to hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while we know of no previous study evaluating patient’s age in association with adverse reactions, one previous study demonstrated that older patients may have stronger reactions to histamine [25]. Finally, the dose of administered iodine has been shown to be associated with iodine allergy [26] ,while chemotoxic reactions are known to be dependent on dose and infusion rate [13]. …”
Section: Discussionmentioning
confidence: 99%
“…22 Generation of molecular iodine from potassium iodide solutions by UV light irradiation. A 4 mL aliquot of 1 mM potassium iodide in 0.1 M phosphate buffer (pH 6.5 or 7.2) was added to 1 mL of 1% soluble starch and was irradiated by UV light in a glass dish of 4-cm diameter with magnetic stirring[113].…”
mentioning
confidence: 99%
“…Shionoya et al[113] studied the effects of UV light on the generation of molecular iodine from iodinated CM. Shionoya et al[113] studied the effects of UV light on the generation of molecular iodine from iodinated CM.…”
mentioning
confidence: 99%
See 1 more Smart Citation